Biochemical liver function tests parameters do not indicate any difference in the degree of hepatotoxicity in patients with metastatic colorectal carcinoma treated with conventional anticancer drugs regardless the use of bevacizumab - Denić, Kristina; Tarabar, Dino; Obradović, Slobodan; Stanić, Nemanja; Spasić, Jelena; Ugrešić, Nenad (Vojnosanitetski pregled, 2017)
Background/Aim. Colorectal carcinoma (CRC) is one the most frequent malignant disease with early liver metastasis. It requires the timely use of anticancer drugs. Current treatment of metastatic CRC consists of conventional anticancer drugs use, but they cause liver damage which is manifested by disorder in biochemical liver function parameters. The addition of one of monoclonal antibodies, e.g. bevacizumab improves their therapeutic effect, but its influence on caused biochemical disturbances is not completely known. Therefore the aim of this study was to compare the level of liver function test parameters in patients treated with conventional anticancer drugs with parameters in patients additionally treated with bevacizumab. Methods. The study was performed on the two groups of adult patients with liver metastatic CRC assigned according to the treatment protocol. One group of the patients (n = 44) was treated with FOLFOX4 (the group 1), and the other one (n = 52) with bevacizumab added to FOLFOX4 treatment protocol (the group 2). Depending on the response of patients, the duration of treatment varied from 2 to 6 months. Standard liver function tests were performed before and after the completion of the treatment. Results. Initial values of some biochemical function test parameters [alkaline phosphatase (ALP) in the group 1 of patients, gamma-glutamyl transferase (GGT) and lactate dehydrogenase (LDH) in both groups] were increased in relation to the normal reference values, with some intergroup differences (p = 0.001). Biochemical disturbances of liver function tests in the group of patients treated with conventional anticancer drugs were due to not only their metastases but also due to the hepatotoxic effect of drugs used. After the treatment, significant differences in biochemical liver tests parameters were found in aspartate aminotransferase (AST), alanine aminotransferase (ALP), GGT and LDH, being lower in the group 2 (patients additionally treated by bevacizumab) (p values were: 0.002 for AST; 0.001 for ALP and GGT; 0.000 for LDH). The levels of the other studied parameters, alanine aminotransferase (ALT) bilirubin, and proteins did not differ significantly between groups both pre- or post-treatment. Conclusion. Both, metastatic CRC and treatment with the conventional anticancer drugs induce significant disturbances of several liver function parameters. The addition of bevacizumab to the conventional anticancer drugs did not affect these disturbances.
Keywords: colorectal neoplasms; neoplasm metastases; antineoplastic combined chemotherapy protocols; antibodies; monoclonal; bevacizumab; liver function tests